1983
DOI: 10.1139/m83-235
|View full text |Cite
|
Sign up to set email alerts
|

Galactosamine inhibition of protein synthesis in Bacteroides thetaiotaomicron

Abstract: Galactosamine does not support growth of Bacteroides thetaiotaomicron. Despite this, galactosamine was more effective than utilizable carbohydrates such as glucose in preventing synthesis of the inducible enzymes alpha-glucosidase and chondroitin lyase. Galactosamine also stopped overall protein synthesis. By contrast glucose and other utilizable carbohydrates increased the rate of protein synthesis. Addition of glucose to bacteria which had been treated with galactosamine restored the ability of the bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Growth yields and maintenance coefficients for colonic Bacteroides growing in continuous culture on polysaccharides have only been determined for one species, B. thetaiotaomicron, and only for two polysaccharides, chondroitin sulfate and arabinogalactan (84,90). In both cases yields were comparable to yields obtained when bacteria were grown on component monosaccharides.…”
Section: Catabolism Of Polysaccharidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Growth yields and maintenance coefficients for colonic Bacteroides growing in continuous culture on polysaccharides have only been determined for one species, B. thetaiotaomicron, and only for two polysaccharides, chondroitin sulfate and arabinogalactan (84,90). In both cases yields were comparable to yields obtained when bacteria were grown on component monosaccharides.…”
Section: Catabolism Of Polysaccharidesmentioning
confidence: 99%
“…In both cases yields were comparable to yields obtained when bacteria were grown on component monosaccharides. High specific activities of a particular polysaccharidase are detected only when the organism is grown on the appropriate polysaccharide (85,87,92). Rev.…”
Section: Catabolism Of Polysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…COOK et al (1965) have shown the incorporation of 14 C-glucosamine into glycoprotein of smooth endoplasmic reticulum and suggested the biosynthesis of surface membrane glycoprotein. Glucosamine has been used for various purposes in bacterial growth media (IMADA et al 1977, SALYERS et al 1983, ROGERS et al 1988, and PLUMBRIDGE et al 1993. In a separate set of experiments when cells were cultured in basal mineral media containing 14 C-glucosamine in presence of Bacitracin (a general inhibitor of glycosylation; 20 µg/ml), the radiolabelling in the dialyzed TCA supernatant fraction, that contains Gp45, decreased significantly (80%) as compared to the controls with out Bacitracin (data not shown).…”
Section: Resultsmentioning
confidence: 97%